2021
DOI: 10.1007/s12015-020-10115-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen- and Progesterone (P4)-Mediated Epigenetic Modifications of Endometrial Stromal Cells (EnSCs) and/or Mesenchymal Stem/Stromal Cells (MSCs) in the Etiopathogenesis of Endometriosis

Abstract: Endometriosis is a common chronic inflammatory condition in which endometrial tissue appears outside the uterine cavity. Because ectopic endometriosis cells express both estrogen and progesterone (P4) receptors, they grow and undergo cyclic proliferation and breakdown similar to the endometrium. This debilitating gynecological disease affects up to 15% of reproductive aged women. Despite many years of research, the etiopathogenesis of endometrial lesions remains unclear. Retrograde transport of the viable mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 186 publications
(253 reference statements)
0
18
0
Order By: Relevance
“…Frontiers in Genetics | www.frontiersin.org June 2022 | Volume 13 | Article 850089 Sarkargar et al, 2021;Szukiewicz et al, 2021). Many studies have demonstrated the influence of genetic and epigenetic modifications on tumor initiation and progression in ovarian cancer, endometrial cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics | www.frontiersin.org June 2022 | Volume 13 | Article 850089 Sarkargar et al, 2021;Szukiewicz et al, 2021). Many studies have demonstrated the influence of genetic and epigenetic modifications on tumor initiation and progression in ovarian cancer, endometrial cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported in the literature that ovarian hormones directly affect the function of the endometrium, and estrogen is a key factor to promote the regeneration and repair of the endometrium and regulate menstruation (12). Progesterone is an important steroid hormone in the body, which interacts with estrogen and periodically acts on the endometrium (13,14). ER and PR are important substances in the female endocrine system, both expressed in the uterus and highly expressed in the endometrium (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dioxin, an omnipresent pollutant, is described as interfering with estrogen signaling through epigenetic modulation [33]. The first experimental data in animal models show an alteration in disease progression by epigenetic modulation, a fact that could be used as a new treatment approach [34,35]. Another still-experimental aspect is the analysis of EM-specific exosomes.…”
Section: Pathogenesis Of Endometriotic Lesionsmentioning
confidence: 99%